Gambaran Klinis Stomatitis Aftosa Rekuren pada Pasien dengan Infeksi Human Immunodeficiency Virus (Laporan Kasus) - Nurfianti Nurfianti; Siti Aliyah Pradono (Majalah Sainstekes, 2019)
Recurrent oral ulceration usually induced pain and influence patient’s quality of life. Reccurent Aphthous Stomatitis (RAS) is a common disorder with recurring ulcers, affecting the oral mucosa, painful and no other signs of systemic disease. Human Immunodeficiency Virus (HIV) is considered as a predisposing factor for RAS. Lesion of RAS associated with HIV, usually more severe, longer lasting to healing and non specific clinical features. This case report describe clinical features of recurrent oral ulceration in HIV patient.  A 23 year old female came with complaint oral ulceration in soft palate and tongue since 2 months ago. Patient was diagnosis HIV since seven years ago. Several examinations were done to explore possibility of opportunist infection in HIV patient. Intra oral examination showed regular ulcer, with yellowish base, surrounding erythematous halo. The locations of ulcer were in labial mucosa, dorsum and ventral of the tongue, and soft palate. Ulceration in keratinized mucosa and non keratinized mucosa, gives un-specific features mimicking Tuberculous oral ulcer but in this case there was no indurations on all ulcer. Based on anamnesis and clinical examination, the diagnosis of this case is RAS with differential diagnosis of Tuberculous oral ulcer. The therapy given was gold standard of RAS, the outcome was successful without TB therapy. RAS on HIV Patient can give unspecific clinical features, mimicking oral manifestation of opportunist infection commonly occurred in HIV patient.